Arquitetura Neocolonial: uma análise arqueológica do discurso nos cenários paulistano e carioca - Lucena, Emanoel Victor Patrício de (2022)
The present research has a theoretical-empirical approach, through which it seeks to analyze the discourse around the Brazilian neocolonial phenomenon, in the theoretical light of the archaeology of discourse proposed by Michel Foucault. The justification of this work is based on contributing to a more accurate understanding of the conflicts and contradictions behind the discourse that led to the emergence of this aforementioned phenomenon in Brazilian context. Adopting the 1900 to 1928 time period as the chronological cut, the research is based on the modernizing and nationalizing zeal of the First Republic in two main centers of cultural effervescence at the beginning of the 20th century: the cities of São Paulo and Rio de Janeiro. In this sense, the work is structured in three chapters. The first presents the historical context that preceded the neocolonial discourse in Brazil, which includes the study of the definition - and relationships between them - of key concepts which have contributed for the understanding of the neocolonial issue in recent historiography of architecture in Brazil. The second chapter is dedicated to the discourse analysis about the neocolonial phenomenon in the contexto of São Paulo, and the third addresses the turnout of that discourse in the carioca context, followed by its analysis. The content presented in the three chapters is based on bibliographic research, documental research and selection of textual corpus, in which the method of archaeological discourse analysis is applied, which primarily seeks to highlight internal and external procedures of control and discursive delimitation. The general objective of the dissertation is to understand the relationships established between the aforementioned modernizing zeal of the Republic and the discourse around the Brazilian neocolonial phenomenon. From that perspective, the results show that from the Proclamation until the early years of the 20th century, the republican nationalist ideal, responding to the alluded effort, prioritized the formation of a sovereign, modern and independent country. Under those circumstances, an anti-Lusitanist spirit developed within the scope of architecture and urbanism, in which any reference to the colonial and imperial past would be considered synonymous with backwardness and subservience. Thus, French Eclecticism was adopted as a bulwark of that republican modernity. Neocolonial architecture in Brazil is, therefore, the result of a discursive arrangement that criticized that ideal of modernity in progress. The aforementioned arrangement was developed in the two main irradiating cultural centers in the country – São Paulo and Rio de Janeiro – from which key figures emerged for the discourse that supported the Neocolonial in national context. In the capital of São Paulo, the work of the Portuguese engineer Ricardo Severo stands out, while in the carioca scenario the work of Araújo Viana, also engineer, and that of José Marianno Filho, doctor from Pernambuco, are well-known. These characters have given a strong contribution to the resignification of colonial architecture as an affirmation of Brazilian nationality, whose main institutional support was the Instituto Histórico e Geográfico Brasileiro (IHGB).